Increasing Customer Loyalty through Customer Experience and Customer Trust (Study on Penataran Train Service Passengers) - Husein, Fachreza Rasyid; Ikut, Camilus Isidorus (Faculty of Economics and Business UNTAG Semarang, 2022)
This study aims to determine the effect of customer experience and trust on customer loyalty who use the services of Penataran Train. The population used in this study were all passengers of the Penataran Railway, whose numbers are unknown for sure, with the number of samples used is 100 respondents. The sampling technique used was accidental sampling. The data source used is primary data, with the data collection method using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of the study showed that the coefficient of determination was 0.518, meaning that customer experience and trust can explain the variation of the customer loyalty variable by 51.8 percent. The results of hypothesis testing are obtained that customer experience has a positive and significant effect on customer loyalty, and trust has a positive and significant impact on customer loyalty.